P129 Skeletal muscle weakness, not arterial stiffness, differs according to GOLD group in COPD. (14th November 2013) - Fisk, M; Gale, N; Mohan, D; Marchong, MN; Forman, J; Lomas, DA; Cockcroft, JR; Bolton, CE; MacNee, W; Fuld, J; Calverley, CM; McEniery, CM; et al.
Abstract : Introduction: In the GOLD 2011 COPD classification, patients in Group D are considered to be at highest risk of mortality, due to airflow limitation and exacerbations and also to be most symptomatic. Skeletal muscle weakness and cardiovascular disease are associated with mortality in patients with COPD and elderly people per se .We hypothesised that GOLD D patients would have more severe extra-pulmonary manifestations of COPD than A-C. Objectives: To measure skeletal muscle weakness and arterial stiffness (an independent predictor of cardiovascular risk) in the ERICA (Evaluating the Role of Inflammation in Chronic Airways Disease) consortium (work package 1) cohort categorised by GOLD Group (ABCD). Methods: ERICA is a multicentre UK study investigating the role of inflammation and the prevalence and significance of cardiovascular and skeletal muscle manifestations in COPD. This interim analysis was conducted on 395 (49%) of 800 planned participants. Measurements include aortic pulse wave velocity (APWV) to measure arterial stiffness, quadriceps maximal voluntary contraction force (QMVC), plasma fibrinogen and 6-minute walk distance (6MWD). We defined arterial stiffness as APWV >10m/s, and skeletal muscle weakness as QMVC/BMI (Body Mass Index) ratio >1.2. Results: 395 subjects were classified according to GOLD groups using the mMRC (modified Medical Research Council) dyspnoea scale to evaluate symptoms, (Table 1 ). The majority of subjects were in groups D (57%) and B (33%), with low numbers observed in groups A (6%) and C (4%). Higher levels of airflow limitation were observed in groups C & D (p = 0.012). Fibrinogen was higher in groups C & D (p = 0.001), consistent with COPD severity. Group D had reduced 6MWD and quadriceps strength consistent with the hypothesis that they have more severe extra-pulmonary manifestations of COPD and increased risk of mortality. Of note, Group B ('high symptom, low risk') also had reduced quadriceps strength and 6MWD, although for 6MWD this reduction (p = 0.06 compared to group A) was not as profound as Group D (p < 0.001). No difference between groups was observed for APWV. Conclusion: The GOLD group classification captures risk related to skeletal muscle weakness but not arterial stiffness and indicates groups B & D may benefit from intensive exercise therapy.